2013
DOI: 10.1111/asj.12113
|View full text |Cite
|
Sign up to set email alerts
|

Lingual antimicrobial peptide and lactoferrin concentrations and lactoperoxidase activity in bovine colostrum are associated with subsequent somatic cell count

Abstract: The present study was undertaken to examine whether potential levels of innate immune factors (lingual antimicrobial peptide (LAP), lactoferrin (LF) and lactoperoxidase (LPO)) in colostrum are associated with subsequent milk somatic cell count (SCC) in dairy cows. Quarter milk samples were collected daily for 1 week postpartum to measure LAP and LF concentrations and LPO activity. SCC in milk was determined weekly for 2 months postpartum and its correlations to concentrations of LAP and LF and LPO activity wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 33 publications
(73 reference statements)
1
11
0
Order By: Relevance
“…Furthermore, the western blot results confirmed that the LAP protein concentration in the HCD group was higher than that in the LCD group and had a strong correlation with its corresponding relative copy numbers of mRNA. Additionally, the finding that the SCC and the LAP protein concentration both increased in the HCD group compared with those in the LCD group is consistent with Kawai et al [ 39 ] and Isobe et al [ 40 ], who found that the SCC is associated with the LAP protein concentration in the milk. Recently, Kawai et al [ 41 ] also found that LF concentration decreased with decrease in SCC after antibiotics treatment, but not LAP concentration and LPO activity, which differed depending on the severity of mastitis.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, the western blot results confirmed that the LAP protein concentration in the HCD group was higher than that in the LCD group and had a strong correlation with its corresponding relative copy numbers of mRNA. Additionally, the finding that the SCC and the LAP protein concentration both increased in the HCD group compared with those in the LCD group is consistent with Kawai et al [ 39 ] and Isobe et al [ 40 ], who found that the SCC is associated with the LAP protein concentration in the milk. Recently, Kawai et al [ 41 ] also found that LF concentration decreased with decrease in SCC after antibiotics treatment, but not LAP concentration and LPO activity, which differed depending on the severity of mastitis.…”
Section: Discussionsupporting
confidence: 89%
“…LF, and S100A7, and for IgA. The measurement methods for LAP, LF, and S100A7 were in accordance with Isobe, Morimoto, Nakamura, Yamasaki, and Yoshimura (2009b), Isobe, Shibata, Kubota, and Yoshimura (2013), and Zhang et al (2014), respectively. The IgA antibody concentrations were determined using the method of Matsukawa, Ueno, and Sugino (2018).…”
Section: Af and Immunoglobulin In The Foremilk Samplementioning
confidence: 80%
“…LF, and S100A7, and for IgA. The measurement methods for LAP, LF, and S100A7 were in accordance with Isobe, Morimoto, Nakamura, Yamasaki, and Yoshimura (2009b), Isobe, Shibata, Kubota, and Yoshimura (2013), and Zhang et al…”
Section: Af and Immunoglobulin In The Foremilk Samplementioning
confidence: 80%
“…The second aliquot of milk was defatted by centrifugation at 1700 × g for 30 min at 4°C and stored at −30°C until the measurement of LAP and LF concentrations and LPO activity (Isobe et al . ).…”
Section: Methodsmentioning
confidence: 97%